BEDANDENG KUTAI: ORNAMENTASI MELISMATIS DALAM BEDANDENG KUTAI - Zamrud Whidas Pratama; Aris Setyoko; Purwanti Purwanti (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
One form of singing or humming that is spread orally is a traditional song or hum that comes from the Kutai tribe called Bedandeng. The purpose of this study was to obtain data on how the history and types contained in the art of Bendadeng. The theory used in this research is historical theory. In addition to the theory about history, the author will also describe the notation of the nyanyain or humming bedandeng. To study it, a qualitative descriptive study was chosen by prioritizing a musicological approach. Data collection is done by (1) literature study, (2) observation, (3) interview, (3) documentation. The stages in analyzing data are (1) data reduction, (2) data presentation, and (3) data analysis (4) conclusion. Clarification of data was again carried out using data triangulation techniques. The results of the study show dandeng or bedandeng is one of the speech arts that exists and develops in Kutai. Bedandeng is a song of lamentation to express what is in the heart. In bedandeng when singing it is not accompanied by any instruments or music and is sung in a recitative way. When viewed from the form of the melody and the lyrics of the bedandeng melody, each melodic phrase has a melismatic ornament. Melismatic ornaments are found at the end of each melodic phrase. It is said to have many melismatic ornaments because in singing Bedandeng, one syllable can be sung with several tones.Kata Kunci: Ornamentasi, Vokal, Bedandeng Kutai.